2020
DOI: 10.1007/s00404-020-05575-6
|View full text |Cite
|
Sign up to set email alerts
|

Term cesarean breech delivery in the first pregnancy is associated with an increased risk for maternal and neonatal morbidity in the subsequent delivery: a national cohort study

Abstract: Purpose To determine whether there is an association between term cesarean breech delivery in the first pregnancy and maternal and neonatal morbidities in the subsequent pregnancy and delivery. Methods We conducted a retrospective, nationwide Finnish population-based cohort study, including all deliveries from January 2000 to December 2017. We included all women with the first two consecutive singleton deliveries of which the first one was a breech delivery regardless of mode of delivery (n = 11,953), and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
(35 reference statements)
1
7
2
Order By: Relevance
“…Our study supports the theory that breech presentation is, in many cases, a symptom of a fundamental problem in fetal morphogenesis or function. 7,8,13 We confirmed and built on existing evidence from earlier smaller studies in which breech presentation at delivery has been demonstrated as a marker for congenital anomalies. 8,10,11,14 However, our results were based on a large sample size.…”
Section: Discussionsupporting
confidence: 77%
“…Our study supports the theory that breech presentation is, in many cases, a symptom of a fundamental problem in fetal morphogenesis or function. 7,8,13 We confirmed and built on existing evidence from earlier smaller studies in which breech presentation at delivery has been demonstrated as a marker for congenital anomalies. 8,10,11,14 However, our results were based on a large sample size.…”
Section: Discussionsupporting
confidence: 77%
“…From the children of women with a previous caesarean preterm breech section had 1.2% an umbilical arterial pH below seven compared to none among the children from women with a history of vaginal preterm breech delivery. This rate was actually higher compared to the results of an earlier study that reviewed the outcome of children among women with a previous term caesarean breech section, among these children had 0.6% an umbilical arterial pH below seven (Macharey et al 2020). The neonates from our study among women with a previous caesarean preterm breech section were more often administrated to the NICU.…”
Section: Discussioncontrasting
confidence: 72%
“…The rate of uterine rupture in our study group was 2.3%, which is relatively high compared to earlier studies that reported rates of 0.7% for low transverse incisions and 2.0% for low vertical incisions (Landon et al 2004). In trials of vaginal birth after previous term caesarean breech delivery, the percentage of uterus rupture is 2.0% (Macharey et al 2020). For T-shaped or classical incision, the risk of uterine rupture during a subsequent pregnancy or birth much higher and ranges from 4% to 9% (ACOG 2010).…”
Section: Discussioncontrasting
confidence: 57%
“…The authors observed delivery mode-related differences in white matter development during infancy, which involved the frontal, temporal, and parietal lobes as well as corpus callosum. Children delivered by cesarean section showed significantly lower white matter development in widespread brain regions and simultaneously lower functional connectivity in the brain [112].…”
Section: Discussionmentioning
confidence: 94%